Reactive Oxygen Species is Associated with Cryptolepine Cytotoxicity (Journal of Science and Technology, 2016)
Cryptolepine (CLP), the major alkaloid of the West African anti-malarial plant Cryptolepis sanguinolenta is a known in vitro mammalian cytotoxin and a DNA intercalator. We have been studying the potential toxicity of CLP and the aqueous anti-malarial formulation (CSE) to mammalian cells in vitro. The objective of the present study was to determine if the cytotoxicity of CLP is as a result of metabolic activation and reactive oxygen species (ROS) generation. Involvement of metabolic activation was assessed by studying the differential toxicity of CLP to MCL-5 and cHoL, two human lymphoblastoid cell lines differing only in their metabolic competencies. ROS determination was performed using the fluorescent probe 2\', 7\'-dichlorofluorescein-diacetate (DCFH-DA), a dye commonly used to measure intracellular changes in ROS. In a Trypan blue exclusion assay, there was no difference between the growth curves of the two cell lines after exposure to CSE (5-100μg/ml) or CLP (0.5-5.0μM) for 24 hours under similar experimental conditions. Further, in an enzyme inhibition assay, CLP at 2.5μM reduced the viability of MCL-5 cells by 30% but the effect of CLP in the presence of inhibitors did not differ significantly from that of CLP alone. In contrast, both CSE and CLP caused a dose-dependent increase in ROS production, which reduced significantly following pre-treatment with N-acetylcysteine, an anti-oxidant. The results together suggest that CLP is a direct cytotoxin that readily generates damaging ROS.